Analysis of sorption and desorption of unsaturated hydrocarbons: Ethylene, propylene and acetylene on hard coals. (15th June 2019) - Dudzińska, Agnieszka
Abstract: Unsaturated hydrocarbons: ethylene, propylene and acetylene are released into the mine atmosphere as a result of the self-heating of coal. Their concentrations in the mine air is one of the indicators for assessing the degree of development of coal self-heating process. The sorption capacity of coals with respect to hydrocarbons may cause their concentrations to decrease in the mine air, which may affect the correct self-heating assessment. This phenomenon is particularly important in the case of coals with a significant sorption capacity. The paper presents the results of studies on sorption of unsaturated hydrocarbons: ethylene, propylene and acetylene carried out on six samples of Polish hard coals taken from the exploited coal seams. High-porous coals with a well-accessible pore system, large specific surface values, low metamorphism and high oxygen content are characterized by the highest sorption capacities. The hydrocarbon sorbed in the largest amount is acetylene, which is due to the smallest size of the acetylene molecule and its high reactivity. The amount of the sorption of ethylene and propylene is lower than that of acetylene and depends on the properties of the coals. Coals with high sorption capacities adsorb larger amounts of propylene than ethylene. For less sorbent coals, the opposite is true. The volume of sorbed hydrocarbons decreases with the increase of the sorption temperature from 298 to 373 K. The temperature has the greatest influence on the volume of sorbed acetylene, the smaller the ethylene. The gas that is the least sensitive to the temperature increase is propylene. On the basis of desorption studies, it has been found that the lowest degree of desorption from coals is displayed by propylene. Higher degrees of desorption were found for acetylene. Ethylene is desorbed the most from coals. The concentration of ethylene in the mine atmosphere is the most frequently used indicator of temperature increase in coal in the self-heating process.